Out of Justice or Charity?: The Fulfillment of the Vow to Serve the Poor in the Company of the Daughters of Charity in the Case of Servant of God Sister Barbara Samulowska, D.C. - Szpoton, Szczepan (Verbum vitae, 2025)
The author of the study reveals the nature and thus the richness of the vows lived out in the Company of the Daughters of Charity. Their specificity comes from the fact that these vows are non-religious, annual, and renewable. Furthermore, they are rooted in the mystery of Christ and the Church. An essential element of the promises made to God by the Daughters of Charity is that these promises are lived by in the light of the vow to serve the poor. The other vows are understood and lived by the sisters in relation to this very vow. Saint Vincent de Paul was convinced that serving the poor was doing justice. In turn, this had to be associated with charity. An example of living by the vow to serve the poor is Sr. Barbara Stanisława Samulowska, D.C. Her just service intertwined with mercy came not so much from the privilege of Marian revelations, which she experienced at Gietrzwałd, but rather from the fulfillment of the charism and aim of the congregation to which she belonged.